Effects of levels of methionine supplementations in forms of L- or DL-methionine on the performance, intestinal development, immune response, and antioxidant system in broilers challenged with Eimeria spp. - Po-Yun Teng; Guanchen Liu; Janghan Choi; Sudhir Yadav; Fengxian Wei; Woo K. Kim (Poultry Science, 2023)
ABSTRACT: The study was conducted to investigate the effects of 2 isoforms of methionine on growth performance and intestinal health induced by methionine (Met) deficiency and Eimeria infection in broilers. A total of 720 one-day old male chicks (Cobb500) were randomly allocated to 10 groups in a 2 × 5 factorial arrangement (6 reps/group, 12 birds/cage) with diets and Eimeria challenge as the main factors. Hundred percent DL-Met, 100% L-Met, 80% DL-Met, and 80% L-Met diets were formulated to meet approximately 100 or 80% of the total sulfur amino acid (TSAA) requirement with DL-Met or L-Met as Met supplementation sources. The 60% TSAA basal diet (60% Met) was formulated without Met supplementation. At d14, the challenge groups were gavaged with mixed Eimeria spp. Growth performance was recorded on d7, 14, 20 (6-day postinfection [DPI]), and 26 (12 DPI). The gut permeability was measured on 5 and 11 DPI. Antioxidant status and gene expression of immune cytokines and tight junction proteins were measured on 6 and 12 DPI. Data were analyzed by 1-way and 2-way ANOVA before and after the challenge, respectively. Orthogonal polynomial contrasts were used for post hoc comparison. Overall, the Eimeria challenge and 60% Met diet significantly reduced growth performance, antioxidant status, and mRNA expression of tight junction genes and immune cytokines. For other Met treatments, the L-Met groups had significantly higher BWG and lower FCR than the DL-Met group from d 1 to 20. The L-Met groups had less gut permeability than the DL-Met groups on 5 DPI. Compared to the 80% Met groups, the 100% Met groups reduced gut permeability. At 6 DPI, the 80% Met groups showed higher ZO1 expression than the 100% Met groups. The challenge groups had higher Muc2 expression and GSH/GSSG compared to the nonchallenge groups, and SOD activity was lower in the L-Met groups compared to the DL-Met groups at 6 DPI. The 100% Met groups had higher GPx activity than the 80% Met groups at 12 DPI. In conclusion, during coccidiosis, the 100% Met groups had better gut integrity and antioxidant status. Met supplementation in the form of L-Met improved growth performance in the starter phase and gut permeability in the challenge phase.